High-pressure processing of bovine milk: Effects on the coagulation of protein and fat globules during dynamic in vitro gastric digestion - He X; Yang M; Yuan F; Singh H; Ye A (Elsevier B V, 2022)
The effect of high-pressure processing (HPP) on the digestion behavior of skim and whole bovine milks was investigated using a human gastric simulator. Both milks formed clots during gastric digestion. HPP treatment led to the formation of a coagulum with a fragmented and crumbled structure, compared with the coagulum formed from untreated milk. At pressures over 400 MPa, more intense pressure resulted in looser and more fragmented gastric clot structures. The weight of the dried clots and the moisture content in the clots of the skim milk treated at 600 MPa were significantly lower and higher than that of untreated skim milk, respectively. The looser and more fragmented gastric clot structures consequently led to faster hydrolysis of the proteins by pepsin during gastric digestion. The denaturation of the whey proteins induced by HPP may have also altered the resistance of α-lactalbumin and β-lactoglobulin in the HPP-treated milk samples to pepsin hydrolysis. This study provides insights into the differences among untreated skim milk, untreated whole milk and HPP-treated milk under in vitro gastric digestion conditions. The structure of the clots formed in the gastric environment affects their breakdown and consequently their emptying rate into the intestine.
Keywords: Bovine milk; High-pressure processing (HPP); In vitro gastric digestion; Protein coagulation